Possibilities of using Mensa puzzles in teaching the gifted - Elijio, Aistė; Abelytė, Lina (Lietuvos matematikos rinkinys, 2012)
The article investigates possibilities to use Mensa puzzles in education of gifted children. Mensa – largest and probably the most famous international organisation of people with high IQ, that includes people of various races, beliefs, age and social background, who pass a special test. In the article, we explore how the puzzles developed by the organization could be applied both working with the students that are gifted in mathematics, and making the usual math lessons at school more interesting.
Keywords: gifted children; Mensa; puzzles